Kapabilitas Digital dan Efek Kepuasan Kerja terhadap Peningkatan Kinerja Karyawan Pondok Pesantren di Jepara - Nur Ahmad Budi Yulianto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Digital transformation is becoming a global challenge for the workforce, where automation with machines and robots has the potential to replace the role of humans in companies. Nonetheless, the success of digital transformation still requires an adaptive workforce with technological skills, which apply in various sectors, including education. The purpose of this study is to determine the influence of digital capability and job satisfaction on the performance of Islamic boarding school employees. This study is a descriptive quantitative research with a population of educators and educational staff of Islamic boarding schools with a total population of 420 employees and which can be used as a sample of 205 employees. Data was obtained through the distribution of questionnaires and then analyzed using WARP PLS 7.0 software. The researchers analyzed that digital skills have an effect on employee performance. Satisfaction has no effect on employee performance and job satisfaction moderates the influence of digital capabilities on employee performance. Recommendations in future studies could include gender differences, a clearer indicator of digital skills.Keyword: digital capability, job satisfaction, job performance, islamic boarding school